Nguyễn Hoàng Châu
l, x^8+x+1 m, x ³ + y ³ -2(x ² - y ²) p, (x ²+x+1)(x ²+x+2)-6
Nguyễn Lê Phước Thịnh
6 tháng 12 2023 lúc 22:16

l: \(x^8+x+1\)

\(=x^8+x^7+x^6-x^7-x^6-x^5+x^5+x^4+x^3-x^4-x^3-x^2+x^2+x+1\)

\(=x^6\left(x^2+x+1\right)-x^5\left(x^2+x+1\right)+x^3\left(x^2+x+1\right)-x^2\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^6-x^5+x^3-x^2+1\right)\)

m: \(x^3+y^3-2\left(x^2-y^2\right)\)

\(=\left(x^3+y^3\right)-2\left(x^2-y^2\right)\)

\(=\left(x+y\right)\left(x^2-xy+y^2\right)-2\left(x-y\right)\left(x+y\right)\)

\(=\left(x+y\right)\left(x^2-xy+y^2-2x+2y\right)\)

p: \(\left(x^2+x+1\right)\left(x^2+x+2\right)-6\)

\(=\left(x^2+x\right)^2+2\left(x^2+x\right)+\left(x^2+x\right)+2-6\)

\(=\left(x^2+x\right)^2+3\left(x^2+x\right)-4\)

\(=\left(x^2+x\right)^2+4\left(x^2+x\right)-\left(x^2+x\right)-4\)

\(=\left(x^2+x\right)\left(x^2+x+4\right)-\left(x^2+x+4\right)\)

\(=\left(x^2+x+4\right)\left(x^2+x-1\right)\)

Bình luận (0)

Các câu hỏi tương tự
18. Đào Gia Hân
Xem chi tiết
Anh Thu
Xem chi tiết
Lê Hoàng Thùy Linh
Xem chi tiết
Trần thị thanh hà
Xem chi tiết
Vương Ngọc Uyển
Xem chi tiết
Tuấn Bảo
Xem chi tiết
Tears
Xem chi tiết
dragom Đức
Xem chi tiết
Ngọc Diễm Nguyễn
Xem chi tiết